A cidade de Fortaleza e suas raízes industriais: ensaios sobre formação urbana e patrimônio industrial - Viana, Flávio Gondim (2015)
According to the Statistical Yearbook of Brazil (1976) the population of Fortaleza went from 41,000 people in 1890 to about 2,571,896 inhabitants in 2014, according to IBGE (2010) and estimates of the resident population of July 2014, published in the Journal Union official on 08/28/2014. This population increase caused rapid expansion of the urban space. From the 1970s the phenomenon of de-industrialization in the urban area of Fortaleza, in addition to causing the transfer of numerous plants to other parts of the city and the state of Ceará, contributed to the closure and abandonment of other areas, some of which are true documentary records of the landscape, identity and symbols that form the local history. On the theme of industrialization and urban space this work aimed to characterize the urbanization of Fortaleza, with reference to the historical context of industrialization from the installation of the first industries in the city. In the text are addressed issues related to industrial heritage, from the reasons why cultural property are not preserved and its implications in the history of communities. Industrialization in Fortaleza seek rescue examples of three ancient city industries: Brazil Oiticica SA , San José Textile Factory ( SA Philomeno Industry and Trade ), and the Oficina do Urubú (Office of the Vulture), belonging to RFFSA, trying to analyze not only the constructed object but the whole process and the circumstances that resulted in him. This literature qualitative study aims not reach conclusive criteria defining categorically that the urbanization of Fortaleza was determined by the arrival of industrialization, but rather to contribute reflections on the theoretical and historical implications of this fact.